Handbook of chemical processing equipment - Cheremisinoff, Nicholas P. (Butterworth-Heinemann, 2000)
Provides descriptions of the working principles, intended applications, selection criteria, and fundamental design principles for equipment used throughout the process and allied chemical industries.
Keywords: Chemical plants -- Equipment and supplies.; elektronické knihy; electronic books